The Influence of Customer Trust on Salwa Minimarket Customer Loyalty with Customer Commitment as a Moderating Variable - Khamdan Suriyok; Arif Syaifudin (Institute of Computer Science (IOCS), 2023)
Based on the results of interviews with several customers of